Draft Fourth Five Year Plan (1969-74) Maharashtra State - Planning Commission (Planning Commission, 1968)
Outlays and expenditure 1966 to 1969, Proposed plan outlays, Important projects costing Rs. 5 crores and above, Check lists in respect of Principal Projects costing Rs. 5 crores and above, Physical programmes.
Government of Maharashtra, Finance Department (Planning)